An In Vitro Pilot Study on the Effects of Silver Diamine Fluoride on Periodontal Pathogens and Three-Dimensional Scaffolds of Human Fibroblasts and Epithelial Cells - Yolanda Ho; Robert Gyurko; Naciye Guzin Uzel; Bjorn Steffensen; Pinelopi Xenoudi; Cheen Loo; Driss Zoukhri (Hindawi Limited, 2022)
Objective. The aims of this study were to investigate the antibacterial and cytotoxic effects of silver diamine fluoride (SDF) on periodontal pathogens and human skin constructs, respectively. Background. SDF has been proven to have bactericidal effects on cariogenic bacteria. No studies to date evaluated the bactericidal effects of SDF on periodontal pathogens nor its effect on epithelium and fibroblasts. Methods. Streptococcus mutans, Porphyromonas gingivalis, and Aggregatibacter actinomycetemcomitans were cultured in monospecies biofilms, exposed to increasing concentrations of SDF and inoculated on agar plates to assess viability. Human gingival fibroblasts in 2D cultures were exposed to 1 μL of 0.394% of SDF and viewed using real-time imaging. Finally, SDF was applied to human, 3D tissue scaffolds of fibroblasts and keratinocytes, and termed human skin equivalents (HSE). A clinical dose of 38% SDF was applied, and HSE were cultured for 12 hours, 1, 3, 5, and 10 days. The tissue was observed clinically and histologically with hematoxylin and eosin staining and TUNEL. Results. S. mutans and A. actinomycetemcomitans growth was completely inhibited using all dilutions of SDF, whereas P. gingivalis was still viable with 0.197% and 0.098% of SDF. Single-layer fibroblasts experienced immediate necrosis upon contact with SDF. Application of SDF to HSE showed maturation of a whitish lesion within 24 hours, followed by pigmented, crusted tissue after 3 days. Histological evaluation of treated tissues showed apoptotic cells in the epithelium and upper half of the connective tissue. Conclusion. Our data suggest that SDF has bactericidal properties against two periodontal pathogens: P. gingivalis and A. actinomycetemcomitans. SDF caused immediate necrosis of monolayer fibroblasts, but does not extend to the full extent of layered fibroblasts in HSE.